(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Moyseuk V. Pedagogical terms of forming of culture of professional health of future social teachers. The article identifying the causes ill health in young student’s age and pedagogical conditions of efficiency of the process creating a culture of occupational health of future social workers.